Annual report to the Government of Grenada 1988 - Instituto Interamericano de Cooperación para la Agricultura (IICA) (Instituto Interamericano de Cooperación para la Agricultura (IICA), 2022)
The report contains the technical cooperations, with their objectives and specific activities carried out in each of the places where attention was focused.